Map : exploring the world - Clarke, Victoria, active 1992; Pickles, Rosie; Cooke, Tim, 1961- (Phaidon Press Limited, 2015)
300 stunning maps from all periods and from all around the world, exploring and revealing what maps tell us about history and ourselves. Selected by an international panel of cartographers, academics, map dealers and collectors, the maps represent over 5,000 years of cartographic innovation drawing on a range of cultures and traditions. Comprehensive in scope, this book features all types of map from navigation and surveys to astronomical maps, satellite and digital maps, as well as works of art inspired by cartography. Unique curated sequence presents maps in thought-provoking juxtapositions for lively, stimulating reading. Features some of the most influential mapmakers and institutions in history, including Gerardus Mercator, Abraham Ortelius, Phyllis Pearson, Heinrich Berann, Bill Rankin, Ordnance Survey and Google Earth. Easy-to-use format, with large reproductions, authoritative texts and key caption information, it is the perfect introduction to the subject. Also features a comprehensive illustrated timeline of the history of cartography, biographies of leading cartographers and a glossary of cartographic terms.